Caprellidae (Crustacea: Peracarida: Amphipoda) from the Red Sea and Suez Canal, with the redescription of Metaprotella africana and Paradeutella multispinosa - Zeina, Amr F.; Guerra-García, José M. (Zootaxa, 2016)
The Caprellidae from the Red Sea are reviewed based on the literature data and new collections from the Hurghada coasts. So far, only six valid species has been reported from the Red Sea and Suez Canal: Caprella equilibra Say, 1818, Hemiaegina minuta Mayer, 1890, Metaprotella africana Mayer, 1903, Paracaprella pusilla Mayer, 1890 and Paradeutella multispinosa Schellenberg, 1928 and Pseudocaprellina pambanensis Sundara Raj, 1927. The type material of M. africana (deposited in the Muséum nacional d’Histoire naturelle, Paris) and Paradeutella multispinosa (deposited in the Museum für Naturkunde, Berlin) are redescribed and illustrated in detail. P. pambanensis and H. minuta were the most abundant species in the collections along the northern coast. Most of the sampling effort has been focused on algae from shallow waters; additional substrates such as sediments, hydroids and coral rubble, especially from areas deeper than 15 meters should be explored. The number of caprellid species in the Red Sea is low compared to adjacent waters, as the Mediterranean Sea. However, further research and more extensive caprellid collections should be conducted along the coasts of Saudi Arabia, Yemen, Sudan and Eritrea, which are still unexplored.